IMPLEMENTASI PROGRAM ADIWIYATA DI SMA N 1 BANGKINANG KOTA KABUPATEN KAMPAR - HAFIZA ELYA ELYA NIRTA; AZHAR AZHAR; HADRIANA HADRIANA (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2017)
The aims of this reaserch are to identify, analyze, and describe the adiwiyata programon Public Senior High School 1 in Bangkinang Kota, starting from the program planning, implementation,and result of the program. This reasearch used a descriptive qualitative approach. Interview anddirect obsevation were done to collect the data. Interview was performed to the school principle,adiwiyata supporting members, teacher board, and students. Direct observation done by observingthe ongoing implementation of adiwiyata program. The results showed that the perception of schoolmembers to adiwiyata program was clearly percieved, followed by good understanding and activeparticipation. Some policies of adiwiyata program already well implemented. Nowadays, adiwiyataprogram were tought in new subject, called PKWU.Utilization of school-environmental basedinfrastructure was well performed. Many tasks done to maintain school environment, utilize, andsupervise the impelemented program. Yet, still some inhibiting factors found by researcher duringimplementation of adiwiyata program, e.g. the impelementation of 4P canteen (plastic, dye, sweetener,preservative). School needs concern participation of all school boards in order to achieve sustainabilityof adiwiyata program implementation.